Transposição didática do estudo de funções de 1°e 2° graus por meio de recursos digitais usando produção de vídeo - Dunnemann, Luzia Correa (Brasil, 2023)
This study was treated at the Maria Ivone de Araújo Leite State Elementary and Middle School in Itacoatiara, Amazonas. With graduating students from Youth and Adult Education – EJA. The objective of this work was to evaluate the production of videos in mathematics class with the theme functions 1st and 2nd degrees domain and co-domain. The students own cell phones with internet and a command application were used. Adapted descriptive statistics and grounded theory to do discuss the observation and data generated. Results liked that students can read content, create scripts, produce videos and respond within standard time.